1998
DOI: 10.1071/pp96014
|View full text |Cite
|
Sign up to set email alerts
|

The influence of atmospheric CO2 concentration on the protein, starch and mixing properties of wheat flour

Abstract: Wheat (Triticum aestivum L.) cultivars Hartog and Rosella were grown at CO2 concentrations of 280 µL L-1 (representing the pre-industrial CO2 concentration), 350 µL L-1 (ambient) and 900 µL L-1 (an extreme projection of atmospheric CO2 concentration). The plants were grown in naturally lit glasshouses in 7 L pots containing soil to which basal nutrients had been added and the pH adjusted to 6.5. Hartog yielded 2.4 g of grain per plant when grown at 280 µL CO2 L-1. This yield was increased by 38% and 75% at CO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…This contrasts with an average 25% reduction in plant dry mass production at subambient [CO 2 ] for a range of species grown at various temperatures (Sage & Coleman, 2001). Nevertheless, our results are supported by a number of studies which reported no growth inhibition in response to decreasing [CO 2 ] from current ambient to preindustrial levels in C 3 plants such as winter wheat (Rogers et al , 1998) and barley (Cunniff et al , 2008). Particularly significant to our study was the report by Rogers et al (1998) that the growth responsiveness to subambient [CO 2 ] depended on the wheat cultivar.…”
Section: Discussionsupporting
confidence: 87%
“…This contrasts with an average 25% reduction in plant dry mass production at subambient [CO 2 ] for a range of species grown at various temperatures (Sage & Coleman, 2001). Nevertheless, our results are supported by a number of studies which reported no growth inhibition in response to decreasing [CO 2 ] from current ambient to preindustrial levels in C 3 plants such as winter wheat (Rogers et al , 1998) and barley (Cunniff et al , 2008). Particularly significant to our study was the report by Rogers et al (1998) that the growth responsiveness to subambient [CO 2 ] depended on the wheat cultivar.…”
Section: Discussionsupporting
confidence: 87%
“…From the current study, and others (e.g. Mandersheid & Weigel, 1997; Hakala, 1998; Rogers et al , 1998; Kimball et al , 2001) it is clear that rising [CO 2 ] is an environmental parameter that results in additional wheat productivity at the whole‐plant level. Preliminary studies for a number of crop species have indicated significant variation in yield among cultivars in response to elevated [CO 2 ] (reviewed in Hall & Ziska, 2000).…”
Section: Discussionsupporting
confidence: 60%
“…(1995) observed a higher proportion of the large A-granules, while Rogers et al (1998) found a higher proportion of the small Bgranules in response to higher CO 2 (Table 2).…”
Section: High Carbon Dioxide (Co 2 )mentioning
confidence: 86%
“…In general, changes in starch morphology and composition were unpredictable (Table 2). It appears that the mode of introducing CO 2 , the concentration and the genotype studied probably influence the data (Rogers et al, 1998). For example, Blumenthal et al…”
Section: High Carbon Dioxide (Co 2 )mentioning
confidence: 98%
See 1 more Smart Citation